Televised video promoting consumption of fruits and vegetables to urban households in Ethiopia - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Developed in consultation with NEED Nutritional Services and tested by IFPRI researchers with 900 households in Addis Ababa. Short summary of the experiment was published in an IFPRI project note. Results were promising enough that the video was broadcast by Sewegna TV Show on Ethiopian television in 2020.